Body Image and Social Anxiety in Late Adolescent Girls of Toraja Ethnicity - Marjori Joy Palpagan; Christiana Hari Soetjiningsih; Enjang Wahyuningrum (Green Publisher Indonesia, 2025)
Body image concerns and social anxiety represent significant mental health challenges among adolescent populations worldwide, with emerging evidence suggesting that these phenomena may be particularly pronounced in specific cultural contexts. Understanding the relationship between body perception and social anxiety in culturally distinct populations is crucial for developing culturally sensitive interventions. This study aims to examine the relationship between body image and social anxiety among late adolescent girls of Toraja ethnicity. A quantitative approach with a correlational design was employed. The participants consisted of 122 female adolescents aged 18–22 years, selected using accidental sampling. The instruments used were the Multidimensional Body Self Relations Questionnaire-Appearance Scales (MBSRQ-AS) and the Social Anxiety Scale for Adolescents (SAS-A). Data were analyzed using the Pearson Product Moment correlation. The results showed a significant negative correlation between body image and social anxiety, with a correlation coefficient of -0.617 and a significance value of 0.000 (p<0.05). This indicates that the more positive the body image, the lower the level of social anxiety experienced by adolescents. Body image contributed 38.06% to the variance in social anxiety. These findings suggest that perceptions of physical appearance play an important role in influencing social anxiety among late adolescent girls. The results further imply that psychological interventions should emphasize self-acceptance and the development of a positive body image to help reduce social anxiety, especially among young females from specific cultural backgrounds.